Counterpoint as a contentive and stylistic device in the intermedial genre (about Viktor Shenderovich’s A Flute Solo) - Lassan, Eleonora (Literatūra, 2019)
In 2015, Vremya Publishing House issued A Flute Solo, a book by V. Shenderovich, a multigenre and, according to the author of the article, intermedial work, since the peculiarities of the content of a political satire and a tragedy, a farce and a fantasy on the one hand and some features of musical pieces, a fugue in particular, on the other hand, have merged there. The author provides a detailed characterization of the plot, constructed as a grotesque depiction of the reality, the composition as relating a verbal text to a piece of music, and the symbolic value of certain elements, allowing not to agree to the definition of the book as being “desperately hopeless”.
Keywords: genre; composition; political satire; counterpoint; intermediality; symbolic text elements